Physico-chemical quality of the water resources in the van region - Sema Ağaoğlu; Süleyman Alemdar; Mustafa Alişarlı; Semiha Dede (Eurasian Journal of Veterinary Sciences)
In the present study, physico-chemical qualities of the water resources such as well, stream, fountain, tap and tank water obtained from the city of Van and its provinces (Erciş, Özalp, Saray, Muradiye, Çaldıran, Gürpınar, Gevaş and Edremit) were investigated. For this purpose, in the spring, summer, autumn and winter seasons, from 100 locations, 366 samples were collected as material, tour times from each spots. In these samples; pH, colour, turbidity, temperature, total roughness, sodium, potassium, calcium, magnesium, chloride, electrical conductivity, carbon dioxide, carbonate, bicarbonate, sulphate, phosphate and organic substance amounts were analyzed. According to the results, turbidity values in the fountain water samples of the city center, its provinces and the tank water samples of the town were not in conformity with the related regulations. Furthermore; chloride, color, turbidity, electrical conductivity and sulphate in the well water, colour and sulphate in the fountain water, total roughness in the stream water of the city centers and towns; magnesium and colour in the stream water, chloride and turbidity in the fountain water of the city center, electrical conductivity in the fountain water of the towns were found to be higher than the values specified in the Turkish Drinking Water Standards. Carbon dioxide levels were also not in acceptable limits established in the quality criteria in all samples.